Market Reaction on Dividend Announcement in Oman- An Event Study Methodology - Rosario, Shireen; Chavali, Kavita (International Journal of Economics and Financial Issues, 2016)
The paper is an empirical study to examine the impact of dividend announcement both cash and stock on the share price performance in Oman. A sample of 21 companies listed in MSM pertaining to different sectors which have made dividend announcement consequently from 2012-2015 are taken. The study adopts the event study methodology. A window of 39 days (19 days prior and 19 days post announcement and dividend announcement date) is taken as to examine the market reaction to the dividend announcement. The findings show that there is an increase in the share price and has resulted in positive average abnormal return especially in the post dividend declaration period in Oman context. Keywords: Dividend announcement, Market Model, market reaction, share price, event study JEL Classifications: G32; G35